Macroprudential Supervision - Challenges for the Insurance Sector - Bednarczyk Teresa, Hanna (Studia Oeconomica Posnaniensia, 2015)
The global financial crisis has exposed the imperfections of the current structure of the financial safety net, based on micro-prudential supervision, targeting the risk reduction of individual financial institutions. The capital requirements relating to financial institutions did not provide sufficient mechanisms for limiting systemic risk. To strengthen the supervisory framework of the financial system, reduce systemic risk and, consequently, reduce the potential impact of financial crises on the economy - the EU introduced regulations forming an Union macro-prudential oversight. Although the insurance industry has not contributed significantly to the financial crisis, it is true that insurance markets are becoming more global and more connected with each other and with financial markets. The aim of this paper is to show the formal and legal framework of the macro-prudential policy and its instruments relating to the insurance sector. The starting point of this paper is to discuss the nature of the macro-prudential instruments. Then to compare the approach of micro and macro-prudential policies. Against this background it will show the legitimacy and implementation of macro-prudential policy instruments in relation to the insurance sector. In the final part some comments on the draft law on macro-prudential oversight of the financial system in Poland are made.